PERLINDUNGAN HUKUM TERHADAP KORBAN PENYEKAPAN DAN EKSPLOITASI ANAK DI KOTA TASIKMALAYA - Robi Assadul Bahri (Jurnal Penelitian Hukum Galunggung, 2025)
The case of child confinement and alleged sexual exploitation in Tasikmalaya highlights persistent weaknesses in Indonesia’s legal protection mechanisms, which are intended to safeguard the safety, dignity, and welfare of children confronted with multilayered forms of victimization. Although Indonesia possesses a relatively comprehensive legal framework, inconsistencies in the application of norms and suboptimal implementation of victim protection provisions reveal a significant gap between the ideal regulatory structure and actual practice. This study aims to assess the adequacy and effectiveness of legal regulations governing child confinement and exploitation through a comparative examination of the Child Protection Law, the Sexual Violence Crimes Law, the former Criminal Code, and the new Criminal Code. Employing a normative legal research method supported by statutory, conceptual, and case approaches, this study conducts norm identification, juridical interpretation, and a comprehensive evaluation of victims’ rights and criminal liability. The findings indicate that the existing legal regime provides sufficient normative grounds for layered prosecution—covering deprivation of liberty, kidnapping, coercion, threats of violence, and sexual exploitation—yet the effectiveness of victim protection ultimately depends on the ability of law-enforcement authorities to formulate integrated charges and consistently uphold victims’ rights. The study concludes that effective child protection requires a multidisciplinary approach that incorporates penal, restorative, and procedural safeguards, along with strong inter-agency coordination to prevent secondary victimization. The practical implications emphasize the need to strengthen institutional capacity, standardize child-sensitive procedures, and ensure enforcement of restitution and rehabilitation as integral components of justice for child victims.